The Roman Empire : a very short introduction - Kelly, Christopher, 1964- (New York : Oxford University Press, 2006)
Offers a brief overview of the Roman empire, discussing the empire's history, imperial mission, art, culture, violent conquests, and lasting impact on world development.
Conquest -- Imperial power -- Collusion -- History wars -- Christians to the lions -- Living and dying -- Rome revisited.
Includes bibliographical references (p. 141-146) and index.
Adult
Keywords: Rome -- History -- Empire, 30 B.C.-284 A.D.; Rome -- Social life and customs; Rome -- History; Rome -- Social life and customs